Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Migration, invasion and decline: changes in recruitment and forest structure in a warming-linked shift of European beech forest in Catalonia (NE Spain) - Penuelas, Josep; Ogaya, Romà; Boada, Martí; Jump, Alistair S. (ECOGRAPHY, 2007)
Altitudinal upward shifts of species' ranges have occurred across a wide range of taxonomic groups and geographical locations during the twentieth century in response to current climate warming. However, actual data of plant species' altitudinal shifts are still scarce and not always clear. Here we provide a more detailed investigation of a previously reported European beech Fagus sylvatica forest altitudinal shift in the Montseny Mountains (Catalonia, NE Spain) now based on field photographic survey and on the population age structure and the recruitment patterns in the high Fagus limit (HFL), the central forest area (CFA) and the low Fagus limit (LFL). Monitoring of the lowest altitudinal range shows that beech forest is being progressively replaced by Mediterranean holm oak forest. Holm oaks are characterized by recruitment rates more than three times higher than those of beech in the LFL in the last decades. The percentage of young individuals in the LFL is only half that in the HFL and CFA. In the highest altitudinal range, present day and early 20th century photographs show that the HFL has gained density and has shifted altitudinally upwards, advancing with establishment of new, vigorous outpost trees (13 individuals per each 100 m of tree-line). They are mostly (89%) younger than 35 yr old and mostly (97%) located up to 70 m (with a few up to 105 m) ground surface distance above the current tree line (36-51 m altitude) at the highest altitudes (1600-1700 m). The beech forest upward shift is a likely consequence of warming, but land-use practice changes (cessation of burning by shepherds) have made it possible. These changes in vegetation distribution and population structure constitute a new indication of the complex global change effects on life in mountain ecosystems.
APSAPSThe following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: altitudinal shifts; climate warming; geographical locations; species ranges; taxonomic groups

Migration, invasion and decline: changes in recruitment and forest structure in a warming-linked shift of European beech forest in Catalonia (NE Spain) - Penuelas, Josep; Ogaya, Romà; Boada, Martí; Jump, Alistair S (ECOGRAPHY, 2007)
Altitudinal upward shifts of species' ranges have occurred across a wide range of taxonomic groups and geographical locations during the twentieth century in response to current climate warming. However, actual data of plant species' altitudinal shifts are still scarce and not always clear. Here we provide a more detailed investigation of a previously reported European beech Fagus sylvatica forest altitudinal shift in the Montseny Mountains (Catalonia, NE Spain) now based on field photographic survey and on the population age structure and the recruitment patterns in the high Fagus limit (HFL), the central forest area (CFA) and the low Fagus limit (LFL). Monitoring of the lowest altitudinal range shows that beech forest is being progressively replaced by Mediterranean holm oak forest. Holm oaks are characterized by recruitment rates more than three times higher than those of beech in the LFL in the last decades. The percentage of young individuals in the LFL is only half that in the HFL and CFA. In the highest altitudinal range, present day and early 20th century photographs show that the HFL has gained density and has shifted altitudinally upwards, advancing with establishment of new, vigorous outpost trees (13 individuals per each 100 m of tree-line). They are mostly (89%) younger than 35 yr old and mostly (97%) located up to 70 m (with a few up to 105 m) ground surface distance above the current tree line (36-51 m altitude) at the highest altitudes (1600-1700 m). The beech forest upward shift is a likely consequence of warming, but land-use practice changes (cessation of burning by shepherds) have made it possible. These changes in vegetation distribution and population structure constitute a new indication of the complex global change effects on life in mountain ecosystems.
APS
Keywords: altitudinal shifts; climate warming; geographical locations; species ranges; taxonomic groups